Relationship Between Nutrition Knowledge and Application of the 4 Pillars of Balanced Nutrition in Employees at PT Multi Kusuma Cemerlang, Samarinda City - Ravika, Devianti; Ratnawati, Ratnawati; Reski, Sepsina (Riviera Publishing, 2022)
A person's level of knowledge influences the application of the four pillars of balanced nutrition. Someone with good nutritional knowledge can easily apply the four pillars of balanced nutrition. A worker with the good nutritional condition will have optimal work quality and better body resistance. This study aims to determine the Relationship between nutritional knowledge and applying the four pillars of balanced nutrition to workers at PT Multi Kusuma Cemerlang in the Palaran working area, Samarinda City. This study uses an analytical observation design with a cross-sectional design. This research was conducted at PT. Multi Kusuma Brilliant. The sample in this study was 54 people who were taken by purposive random sampling. Data were obtained using a questionnaire and tested with fisher's statistical test. The results showed no significant relationship between nutritional knowledge and the application of the four pillars of balanced nutrition; the p-value was 1.000 (p>0.05). There is no significant relationship between nutritional knowledge and applying the four pillars of balanced nutrition to workers at PT. Brilliant Multi Kusuma